Pengaruh Kecanduan Game Free Fire terhadap Etika Komunikasi Siswa MTS Nurul Aeyn As’adiyah Kampung Baru di Bone: The Effect of Free Fire Game Addiction on Communication Ethics of MTS Nurul Aeyn As'adiyah Kampung Baru Students in Bone - Irwandi; Sanatang; Nurul Mukhlisah Abdal (Jurnal Pendidikan Terapan, 2025)
This study aims to determine the effect of Free Fire online game addiction on the communication ethics of class IX students at MTs Nurul Aeyn As'adiyah Kampung Baru in Bone. The method used is quantitative with an ex post facto approach. A sample of 38 students was taken using purposive sampling technique. The research instrument is a questionnaire that has been tested for validity and reliability. The results of the analysis show that the level of addiction to the Free Fire game is in the high category (52.6%) and has a significant negative effect on students' communication ethics, with a Pearson correlation value of -0.829 and a significance of 0.000. A total of 68.8% of the variation in communication ethics is explained by the level of game addiction. The conclusion of this study shows that online game addiction has a negative impact on communication ethics, such as the use of harsh language, unstable emotions, and low politeness when interacting.